Identifying Business Potential for Small and Medium-Sized Enterprises (SMEs) Based on Developmental Plans in Penang, Malaysia - Mat Radzi, Rafisah; Yaacob, Zulnaidi (Journal of Technology Management and Business, 2022)
This study aims to identify the business potential possibilities for small and medium-sized enterprises (SMEs) and explore the ways in which such businesses and state, regional and national economic development planning may interact. Drawing insights from Penang’s development plans and/or blueprints, this paper generates a typology of such plans and maps them accordingly in terms of economic sector. In capturing the national and state development plan and/or policies for its economic progress, research methodology through a content analysis was done by referring to the documents issued by Penang and national agencies The strategies will help equip a way forward for SMEs to grow in response to these development plans. By participating in the main economic sectors this strategy will directly bring benefits for SMEs’ as they will be able to have wider access to markets, including government programs and incentives. When SMEs align their business model with what an economy is trying to achieve policy-wise, this endeavor will to a certain extent mitigate the common challenges that hinder SMEs’ growth.